2007
DOI: 10.1063/1.2822333
|View full text |Cite
|
Sign up to set email alerts
|

The pressure-dependent performance of a substrate-free focal plane array in an uncooled infrared imaging system

Abstract: Uncooled focal plane arrays (FPAs) are being developed for a wide range of infrared imaging applications. A substrate-free FPA for optical readout infrared imaging is fabricated with a pixel pitch of 120 μm. The pressure dependences of thermal conductance of a FPA with/without substrate are studied by modeling analysis. Infrared imaging experiments are performed to validate the modeling analysis. At atmospheric pressure the total thermal conductance of the substrate-free FPA is only 1/1000 time of the traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Meanwhile, considering that there are always groups of pixels simultaneously absorbing IR radiation, the temperature change of 1.224 K is a reasonable choice to evaluate the fabricated FPA. Hence, the IR radiation conversion efficiency can be estimated to be 6.81%, which is increased by about 6.2 times compared with the analytical result (0.94%) [8], [9] of the substrate FPA.…”
Section: Simulation and Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Meanwhile, considering that there are always groups of pixels simultaneously absorbing IR radiation, the temperature change of 1.224 K is a reasonable choice to evaluate the fabricated FPA. Hence, the IR radiation conversion efficiency can be estimated to be 6.81%, which is increased by about 6.2 times compared with the analytical result (0.94%) [8], [9] of the substrate FPA.…”
Section: Simulation and Discussionmentioning
confidence: 76%
“…The finite-element analysis indicated that, benefiting from the temperature-variable supporting frame, the temperature of the bimaterial legs in the deformation-magnifying structure is close or even equal to the temperature of the IR absorber. Therefore, the efficiency of the deformation-magnifying structure can be maximized, and our analytical calculation yielded Δθ/ΔT c of 0.2 • /K, which was increased by 33.3% compared with the value of 0.15 • /K of the substrate FPA, where there is a temperature gradient between the supporting frame and the IR absorber [8], [9].…”
Section: Simulation and Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A conducting heat exchange between the paddle of the can− tilever and the substrate's surface through air does not occur. The USTC/CAS group and also Grbovic have suc− cessfully demonstrated thermal imaging with a substrate− −free thermomechanical microcantilever FPA operating at atmospheric pressure [84,110]. However, the image quality of FPAs operating in air is poor, mainly due to the decreased microstructures' Q−factor.…”
Section: Developments In Chinamentioning
confidence: 99%
“…As in the finite element analysis, the thermal conductance of the FPA ͑including radiative heat exchange͒ was simulated, but air convection was neglected for the vacuum environment ͑Յ1 Pa͒. 13 The other assumptions used in the finite element analysis also included the incident heat flux of 10 pW/ m 2 , according to which the temperature change of IR targets ⌬T S can thus be estimated to be 17.97 K, 14 and the temperature boundary condition was constant at 298 K.…”
Section: A Finite Element Analysismentioning
confidence: 99%